Impact of tree species replacement on carbon stocks in forest floor and mineral soil - Fonseca, Felícia (2011)
The increase in atmospheric carbon content, as expected considering actual trends, draws attention to the highly valuable role of forest ecosystems in the global carbon cycle. Accordingly, the carbon storage capacity by different species should be a decision support tool when introducing new forest species. This study aims at evaluating the influence of replacing areas of Quercus pyrennaica, which represents native vegetation of Serra da Nogueira, in the northeast of Portugal, by Pseudotsuga menziesii on carbon stocks in forest floor and mineral soil. Three sampling areas were selected in adjacent locations with similar soil and climate conditions. The first area, covered by Quercus pyrennaica (QP), represents the original soil. The second area is in a 40 years old stand of Pseudotsuga menziesii (PM40), and the third one, also under Pseudotsuga menziesii, is 15 years old (PM15). In each sampling area, at 10 randomly selected points, samples were collected in the forest floor (0.49 m2 quadrat) and in the soil (at 0-5, 5-10 and 10-20 cm depth). Results show that carbon concentration is significantly higher in forest floor under native species (QP), but the amount of organic residues accumulated on the soil surface is higher under the introduced specie (PM40 and PM15). The forest floor stores 17, 13 and 6% of total carbon for PM40, PM15 and QP, respectively. Four decades after species replacement, a soil organic carbon loss is observed, although no significant differences were found when comparing soil under introduced (PM) with original species (QP). A carbon loss of around 30%, in PM15, and gains of about 10%, in PM40, are computed when considering mineral soil and forest floor together. As shown by results, in PM, forest floor was a carbon sink whilst mineral soil was a carbon source.